Suppression of gamma(1S), gamma(2S), and gamma(3S) quarkonium states in PbPb collisions at root S-NN=2.76TeV - (:unkn) unknown (ELSEVIER, 2017)
The production yields of gamma(1S), gamma(2S), and gamma(3S) quarkonium states are measured through their decays into muon pairs in the CMS detector, in PbPb and pp collisions at the centre-of-mass energy per nucleon pair of 2.76TeV. The data correspond to integrated luminosities of 166 mu b(-1) and 5.4 pb(-1) for PbPb and pp collisions, respectively. Differential production cross sections are reported as functions of gamma rapidity y up to 2.4, and transverse momentum PT up to 20 GeV/c. A strong centrality-dependent suppression is observed in PbPb relative to pp collisions, by factors of up to approximate to 2 and 8, for the gamma(1S) and gamma(2S) states, respectively. No significant dependence of this suppression is observed as a function of y or PT. The gamma(3S) state is not observed in PbPb collisions, which corresponds to a suppression for the centrality-integrated data by at least a factor of approximate to 7 at a 95% confidence level. The observed suppression is in agreement with theoretical scenarios modeling the sequential melting of quarkonium states in a quark gluon plasma. (C) 2017 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Heavy ions; Dimuons; Bottomonia; CHARMONIUM SUPPRESSION; PSI-SUPPRESSION; HEAVY; PROTON; J/PSI